Intriguing haemorrhages: a review of last seven decades (1951-2021) - Saha, Biswajit (International Journal of Research in Medical Sciences, 2021)
Bleeding as a cause of underlying psychological or psychiatric disorder is hardly ever thought of mainly due to unawareness and rarity. An overview will help to understand the real problem. A detailed literature survey of different types of bleeding from various parts of the body for which the reasons could not be diagnosed easily was made over last seven decades (1951-2021). These have been presented mainly in tabular form and also, in the text as briefly as possible to have a comprehensive overview only. The contents portray the nature, triggers and spectrum of settings in which haemorrhages occurred including the explanations which were available from the articles. In addition, some of my personal conjectures as possible causes have also been included. Unexplained bleeding might be psychological or psychiatric in origin. Awareness about this will enable to diagnose the case at the earliest and accordingly, the management can be started. Different types of such haemorrhage including particularly those due to idiopathic causes are potential areas of research.